Specialization in juvenile careers: Markov results for a California cohort - Lattimore, Pamela K. (Journal of quantitative criminology, 1994)
In this paper, we examine the arrest careers through September 1985 of a highly active cohort of youth paroled by the California Youth Authority in the early 1980s. Our results are in some ways similar to and in other ways different from those reported by other researchers. We find that while adjacent transition matrices appear constant, the same cannot be said for nonadjacent matrices. We reject the first-order Markov hypothesis and find support for specialization in the statistical significance of the forward specialization coefficients. Our results also suggest that, in addition to transitions to the same type of offense, an oscillating pattern of offending is common for our subjects. We also compare the transition matrices of three racial/ethnic and four regional groups. These results indicate differences in the patterns of offending by the racial/ethnic groups in our sample and similar offense-transition behavior in three of the four regions that differs significantly from that of the fourth region.